Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
Вот решение:
( 2х - 3 ) ^ 2 - ( 1 - 2х ) ^ 2 = 0
далее по формуле разности квадратов
( 2х - 3 + 1 - 2х ) * ( 2х - 3 - 1 + 2х ) = 0
-2 * ( 4х - 4 ) = 0
4х = 4
х =1
можно конечно в квадрат возвести
4х ^ 2 - 12х + 9 = 1 - 4х + 4х ^ 2
8х = 8
х =1
вот так
( 2х - 3 ) ^ 2 - ( 1 - 2х ) ^ 2 = 0
далее по формуле разности квадратов
( 2х - 3 + 1 - 2х ) * ( 2х - 3 - 1 + 2х ) = 0
-2 * ( 4х - 4 ) = 0
4х = 4
х =1
можно конечно в квадрат возвести
4х ^ 2 - 12х + 9 = 1 - 4х + 4х ^ 2
8х = 8
х =1
вот так
0
·
Хороший ответ
17 января 2023 03:09
Остались вопросы?